Shades that captivated. Dyestuff in al-Andalus and textile colours in medieval Castile (ca. 1200 – ca. 1385) - Barrigón, María (De Medio Aevo, 2026)
This article adresses the colours appearing in medieval textiles, those being a significant factor contributing to their value. It focuses on the time period from 1200 to 1400 in the Crown of Castile. The historical Castilian documentary sources enable us to identify the names of some of the dyestuffs and also above all, the use of colour adjectives. The ultimate goal is to collate data regarding the colours’ names that expressed the shades obtained by various dyestuffs in the textiles of that historical period and region. This research enhances our comprehension of the historical textile colour terminology.